ANALISIS PENERAPAN MODEL PEMBELAJAR THE POWER OF TWO MATERI PENCEMARAN LINGKUNGAN DI SMA NEGERI 11 LUWU UTARA - Rosnawaty, Eka; Asri; Yulyani Wardi , Ridha (Jurnal Biogenerasi, 2024)
The research objective of implementing learning actions using the power of two learning model on environmental pollution material at SMA Negeri 11 Luwu Utara is to increase understanding of environmental pollution knowledge, it is hoped that students will have awareness so as not to participate in polluting the environment, which until now has become a national problem. The type of research used is action research which is directly applied in the classroom by direct appointment (purposive sampling). The method used uses four steps, namely: (1) planning step, (2) action step, (3) observation step, (4) reflection step. The research results obtained are: (1) the results of learning using the power of two model on environmental pollution material for the first course obtained an average score of 55.16, but no students passed according to the KKM standard ≥73. Continuing with action two, an average score of 84.61 was obtained. If this score is confirmed by the KKM standard, the learning outcomes will be 100% complete; (2) The observer's assessment of learning management in four meetings, if it is confirmed that the implementation criteria are in the interval 3.50 ≤ x ≤ 4.00, then the implementation of category learner management is carried out well. It was concluded that applying the power of two model to environmental pollution material could significantly improve learning outcomes.